Influence of Influencer Credibility on Consumer Attitude Towards Product and Advertising, and Its Impact on Purchase Intention - Prasetya, Dimas; Wahyudi, Triyono Arief (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
This study analyzes the influence of influencer credibility on attitude towards product and attitude towards advertising, as well as its impact on purchase intention in the automotive industry on the YouTube platform. The research employs an online survey with 168 respondents who follow automotive influencers. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that influencer credibility positively affects attitude towards product but does not influence attitude towards advertising. Furthermore, attitude towards product and attitude towards advertising positively impact purchase intention. These findings suggest that while influencer credibility can enhance a positive attitude toward a product, it does not necessarily lead to greater acceptance of advertisements. The study's implications highlight the importance of selecting influencers with strong reputations and expertise to enhance consumer attitudes toward products and increase purchase intention. Additionally, companies should ensure that their marketing strategies include engaging and relevant advertisements for their target audience.